Priming response in male Schizothorax richardsonii to the ovarian steroid glucuronides from conspecific and heterospecific females - BHATT, J P; PUROHIT, M K; NAUTIYAL, R; KANDWAL, J S (The Indian Journal of Animal Sciences, 2014)
Ovarian steroid glucuronide is used as sex pheromone by males of 3 sympatrically spawning species of Himalayan trout. Mature males of Schizothorax: richardsonii, Schizothorax plagiosiomlls and Schizothorax sinuatus were exposed to the ovarian odours from ovulated conspecific and hetcrospecific females. Ovarian odour of each species had a significant priming effect (increased GSI, milt volume, spermatocrit and sperm motility) on conspecific males. Male Schizo/horax richardsonii expressing a significant priming response to the ovarian odours from both heterospecific female species is suggesting the lack of species specificity to sex steroids in this ush. The mature males of Schizothorax plagiostomus and Schizothorax stlluatlls did not exhibit the priming response to the ovarian odours of heterospecific females. No performance of the spawning acts by male Schizothorax: richardsonii with heterospecific females if conspecific females are present possibly might be strategy to maintain the reproductive isolation in a spawning territory.